Variacin, a new lanthionine-containing bacteriocin produced by Micrococcus varians: comparison to lacticin 481 of Lactococcus lactis. - Pridmore, D (1996)
A new lanthionine-containing bacteriocin, variacin, displaying a broad host range of inhibition against gram-positive food spoilage bacteria, has been identified from two strains of Micrococcus varians isolated from meat fermentations. The new bacteriocin was purified, and its amino-terminal end and total amino acid composition were determined. The structural gene was isolated and analyzed. Variacin is resistant to heat and pH conditions from 2 to 10. Its primary sequence shows significant homology to lacticin 481 to Lactococcus lactis, which is more pronounced for the probacteriocin than for the leader sequence. Variacin, like lacticin 481, contains lanthionine and beta-methyllanthionine residues, but its leader sequence clearly resembles nonlantibiotic leader sequences. In particular, the prepeptide contains glycine residues at positions -1 and -2 of the processing site.